2019
DOI: 10.1530/erc-19-0075
|View full text |Cite
|
Sign up to set email alerts
|

Enriched environment inhibits breast cancer progression in obese models with intact leptin signaling

Abstract: Obesity is becoming a global epidemic and is a risk factor for breast cancer. Environmental enrichment (EE), a model recapitulating an active lifestyle, leads to leanness, resistance to diet-induced obesity (DIO) and cancer. One mechanism is the activation of the hypothalamic–sympathoneural–adipocyte (HSA) axis. This results in the release of norepinephrine onto adipose tissue inducing a drop of leptin. This study aimed to test the effects of EE on breast cancer onset and progression while considering the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…We are currently investigating whether the HSA axis affects the chronic low grade inflammation associated with obesity that is linked to increased cancer risk. Collectively, our series of studies support the notion that environmental or gentic activation of the HSA axis can ameliorate obesity in genetic ( 6 , 38 , 40 ) and diet-induced ( 6 , 28 , 38 , 39 , 41 ) mouse models, and inhibit cancer growth and metastasis.…”
Section: Targeting the Hsa Axis For Treatment Of Obesity And Cancersupporting
confidence: 76%
See 1 more Smart Citation
“…We are currently investigating whether the HSA axis affects the chronic low grade inflammation associated with obesity that is linked to increased cancer risk. Collectively, our series of studies support the notion that environmental or gentic activation of the HSA axis can ameliorate obesity in genetic ( 6 , 38 , 40 ) and diet-induced ( 6 , 28 , 38 , 39 , 41 ) mouse models, and inhibit cancer growth and metastasis.…”
Section: Targeting the Hsa Axis For Treatment Of Obesity And Cancersupporting
confidence: 76%
“…DIO accelerated PyMT mammary tumor progression in SE whereas EE effectively alleviated DIO and significantly delayed the occurrence of palpable tumor in spontaneous MMTV-PyMT mice. EE also inhibited transplanted PyMT primary tumor progression in wild type DIO mice, but not in the leptin-defective Ob/Ob mice, again confirming the role of leptin ( 38 ).…”
Section: Targeting the Hsa Axis For Treatment Of Obesity And Cancermentioning
confidence: 57%
“…noted they did not see a change of the level of circulating IL‐15 in EE mice [19], we are currently examining whether EE affects different forms of IL‐15 in various tissues and organs. Moreover, our previous studies reveal profound remodeling of the adipose tissue upon exposure to EE [9, 11, 12, 14, 15] including decreased leptin levels and increased adiponectin levels. These adipokines play important roles in the communication between the neuroendocrine and immune systems [35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to the standard housing (SE) used in most biomedical research facilities, the EE is a housing environment that provides social, physical, and cognitive stimulation and has a significant influence on the brain function and progression of neurological diseases [10]. We have previously demonstrated that EE leads to anticancer and anti‐obesity phenotypes in various mouse models and identifies a specific brain–fat axis as a key underlying mechanism [9, 1115]. More recently, we have investigated how EE regulates T cell immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Mice living in the enriched housing environment showed less tumor growth and more frequent remission in melanoma and colorectal cancer, caused by elevated serum brain-derived neurotrophic factor (BDNF) and markedly lower leptin concentrations ( Cao et al, 2010 ). Interestingly, EE inhibits mammary tumor growth rate with intact leptin signaling in diet-induced obesity models ( Foglesong et al, 2019 ). In pancreatic cancer, EE was reported to significantly reduce tumor weight in subcutaneous and orthotopic mouse models via down-regulation of the expression of mitochondria-related genes ( Li et al, 2015 ).…”
Section: Regulation At the Central Levelmentioning
confidence: 99%